1998
DOI: 10.4049/jimmunol.161.2.897
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Mediated, IFN-γ-Facilitated Rejection of Murine B16 Melanomas

Abstract: The murine melanoma cell line B16.F10 (H-2b) was used to study specific T cell responses that reject tumors. Stable B16 transfectants were established that express viral Ags, either the hepatitis B surface Ag (HBsAg) or the large tumor Ag (T-Ag) of SV40. B16 cells and their transfected sublines were CD40+CD44+ but expressed no (or low levels of the) costimulator molecules CD154 (CD40L), CD48, CD54, CD80, and CD86. Surface expression of MHC class I (Kb, Db) and class II (I-Ab) molecules by B16 cells was low, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Both human melanomas and B16 can often be induced to express MHC Class II by IFN-γ treatment. (Bohm et al, 1998;Surman et al, 2000) Humans can survive for months or years despite melanoma growth; a minimal tumorigenic dose of B16 melanoma (intravenous or subcutaneous) will kill an untreated mouse within weeks.…”
Section: Similarities Differencesmentioning
confidence: 99%
“…Both human melanomas and B16 can often be induced to express MHC Class II by IFN-γ treatment. (Bohm et al, 1998;Surman et al, 2000) Humans can survive for months or years despite melanoma growth; a minimal tumorigenic dose of B16 melanoma (intravenous or subcutaneous) will kill an untreated mouse within weeks.…”
Section: Similarities Differencesmentioning
confidence: 99%
“…For B16F10, two immunopeptidomics datasets were generated using IFNy-stimulated cells and in vivo grown tumors. Unstimulated B16F10 cells were not analyzed as previous studies have reported poor MHC presentation on unstimulated B16F10 cells 23 . A total of 7078 unique sequences without PTMs were identified across the two datasets (Figure S1G).…”
Section: Resultsmentioning
confidence: 99%
“…The B16F10 murine syngeneic tumor cells have low levels of MHC-I antigen presentation at cell surface 30 and are infiltrated with low numbers of T cells when grown as subcutaneous tumors in vivo, 31 representing the immunologically cold tumor phenotype observed in human cancers that tend to be refractory checkpoint inhibitor treatment. B16F10 has been widely reported to be resistant to checkpoint inhibitors, including anti-CTLA-4, anti-PD-1, and anti-PD-L1 mAbs when given as monotherapy treatments.…”
Section: Discussionmentioning
confidence: 99%